Ef fect of native microorganism ef ficacy and compost in three altitudinal zones on quinoa crop (Chenopodium quinoa) variety INIA 415-Pasankalla - Galecio-Julca, Miguel; Neira-Ojeda, María; Chanduvi-García, Roger; Peña-Castillo, Ricardo; Álvarez-Bernaola, Luis Armando; Granda-Wong, Carlos; Lindo-Seminario, David; Saavedra-Alberca, Elizabeth; Javier-Alva, Javier; Morales-Pizarro, Davies Arturo (REVISTA TERRA LATINOAMERICANA, 2023)
Organic fertilizers are a sustainable alternative to conventional fertilizers that cause contamination of natural resources. The objective of this study is to determine the ef ficacy of native microorganisms (ENM) and compost on yield and profitability on the cultivation of quinoa variety INIA 415-Pasankalla in three altitudinal levels (Faical 1935 m altitude, Lagunas Amarillas 2328 m altitude and Cascapampa 2995 m altitude). Five treatments were evaluated: T0 (control), T1 (MEN 2.5%), T2 (MEN 5.0%), T3 (MEN 2.5%+0.9 kg compost m-1) and T4 (MEN 5.0%+1.8 kg compost m-1), considering: PA (plant height), RHa (yield per hectare), RPa (yield plant-1), PP (panicle weight), PMG (thousand kernel weight) and DT (stem diameter). In addition, the benefit/cost per treatment was analyzed. A principal component analysis (PCA), three-way ANOVA comparison and correlation analysis were performed. The PCA yielded two components (C1 and C2) explaining 97.20% of the variability of the study. Component 1 (78.46%) explained the greatest variability and grouped the variables: G-I (AP, DT), G-II (RHa, Rpa, PP). Treatments T4 and T3 showed the best results in relation to altitude: Lagunas Amarillas-T4 with G-I and Cascapampa-T4 with G-II showed the highest study values. However, Cascapampa-T2 was the most profitable (b/c= 5,68). The combined mixture of organic inputs made from local raw materials and applied in foliar form, and the soils present in T4, improved the yields and profitability of the quinoa crop in relation to altitude.